IMPLEMENTASI MATERI NORMA DAN HUKUM UNTUK PENCEGAHAN BULLYING DI SMPN 5 MUARO JAMBI - Haviza, Nur; Warna, Eka; Melisa, Melisa (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to provide an overview of efforts to implement norm and law materials for bullying prevention at SMP N 5 Muaro Jambi and, To determine the supporting and inhibiting factors for the implementation of norm and law materials for bullying prevention at SMP N 5 Muaro Jambi. This research was carried out at SMPN 5 Muaro Jambi, located on Jl. lintas Sumatra No.RT.09, Sekernan, Kec. Sekernan, Muaro Jambi regency, when the research was carried out in the even semester of the 2022/2023 academic year. The research approach used in this study is a qualitative approach. The type of research used in this study is Case study The data collected in this study is descriptive. The results showed that in an effort to implement norms and laws for the prevention of bullying at SMP N 5 Muaro Jambi which was carried out through learning activities in the classroom and activities outside the classroom using the following methods or strategies: a) Exemplary To shape the character of students who obey norms and non-violence through the example ofteachers b) Spontaneous activities Including disciplinary activities c) Conditioning, in the nature of implementing norms and laws for the prevention of bullying in schools in order to form civic knowledge it occurs because there aresupporting factors and inhibiting factors.Supporting factors consist of awareness of school residents to apply positive norms on various occasions, inhibiting factors consist of student conditions that are still unstable.